Two new species and new findings in the genus Pallenopsis (Pycnogonida: Pallenopsidae) with an updated identification key to Antarctic and Sub-Antarctic species - Cano-Sánchez, Esperanza; López-González, Pablo J. (Zootaxa, 2019)
The present contribution describes and discusses the observed morphological variability of pycnogonids in the genus Pallenopsis collected during the Italica XIX cruise to Victoria Land, Ross Sea, Antarctica (3 Feb-4 Mar, 2004). Four species are recognized in this collection and two of them are proposed as new species Pallenopsis gracilis n. sp. and Pallenopsis rotunda n. sp. The new species are described, illustrated, and compared morphologically with their closest congeners. The morphological diagnostic characters of the subgenus Bathypallenopsis are discussed and considered insufficient to justify a separation into subgenera. The observed morphological variability is instead proposed to be accommodated in one inclusive genus Pallenopsis. Finally, we propose an updated dichotomous key to all currently recognized Antarctic and Sub-Antarctic Pallenopsis species (adult form), and discuss some of the more disputable taxa, highlighting the lack of knowledge of the morphological and molecular characters of this genus.